Outcome of Primary Intracerebral Hemorrhage: Study in a Tertiary Care Center in Western Nepal - Gautam, Subodh; Sah, Niraj Prasad; Nepal, Ashmita; Jha, Sumi; Siddiqui, Saharoj; Tiwari, Jonesh (Nepal Journal of Neuroscience, 2026)
Background: Primary intracerebral hemorrhage (ICH) is a leading cause of stroke-related mortality in South Asia, yet data from western Nepal remain limited. This study describes the clinical profile, radiological characteristics, management strategies, and three-month outcomes of primary ICH patients at a tertiary care center in western Nepal. Material & Methods: This prospective analytical study was conducted at the Department of Neurosurgery, Nepalgunj Medical College and Teaching Hospital (NGMCTH), Kohalpur, Nepal. Sixty-three adult patients with confirmed primary ICH on non-contrast CT head were enrolled over three months using consecutive sampling and followed up for an additional three months. Clinical, demographic, and radiological data were collected at the time of admission. Neurological status was assessed using the Glasgow Coma Scale (GCS) at admission and at three months. Results: The median patient age was 62 ± 12.8 years, with male predominance (65.1%). Hypertension was the most common comorbidity (74.6%). 74.6% presented with moderate-to-severe neurological compromise. Admission GCS was significantly associated with three-month neurological outcome. Conservative management was employed in 63.5% of patients, and 17.5% underwent surgical intervention. A notable 25.4% left against medical advice (LAMA). Conclusion: Primary ICH in western Nepal predominantly affects middle-aged hypertensive males. Admission GCS is the strongest predictor of short-term neurological outcome. The high LAMA rate reflects critical socioeconomic barriers that likely underestimate true ICH mortality. Strengthening community-level hypertension control, expanding financial protection for neurosurgical emergencies, and improving patient retention seem essential to improving outcomes in this region.